Meaning, desire, and God: an expansive naturalist approach. Issue 4 (20th October 2021) - Ellis, Fiona
ABSTRACT: I offer an approach to the problem of life's meaning which poses a radical challenge to some of the familiar terms of this debate. First, I defend an expansive form of naturalism which involves a rejection of the common assumption that naturalism and theism are logically incompatible and offers a framework from which to rethink some of the central concepts operative in discussions of life's meaning. Second, I defend a 'desire solution' to the problem of life's meaning. My initial inspiration is Richard Taylor's version of such a position as articulated in his book Good and Evil . I argue that this solution is best articulated from within an expansive naturalist framework, raise some doubts about Taylor's metaphysics, and make a connection with the Nietzschean problem of nihilism.